Demographic Factors Affecting the Job Satisfaction of Mathematics Teachers: A Case Study of Kathmandu Municipality - Adhikari, Ganesh Prasad (Academia Research Journal, 2023)
Job satisfaction is a crucial factor for professionals. Job satisfaction among teachers reflects their high levels of professional motivation. This study investigated the effect of demographic factors on job satisfaction among secondary mathematics teachers in the Kathmandu Municipality. In quantitative research, a cross-sectional survey research design was used in this study. The data was collected through a validated structural questionnaire, which consisted of ten items on job satisfaction and eight demographic variables. The structural questionnaire was administered to a sample of 136 mathematics teachers over the course of one month (17 August–16 September). Data were entered in SPSS Version 26, and frequency, percentage, and multiple linear regression were used in the analysis of the data. The results of this study revealed that there is no statistically significant effect of demographic variables on the job satisfaction of mathematics teachers. Based on the findings of this study, I contend that demographic variables have no effect on job satisfaction among mathematics teachers. The study's limitations include the fact that demographic variables (gender, age, school type, school area, teaching experiences, educational level, and job position) explained only 6% of the variation in job satisfaction. Future research should be done on a larger scale to increase the number of demographic variables and sample sizes in other parts of Nepal and by other subjects' teachers. Similar studies could be done with basic-level and university-level mathematics teachers in Nepal.